Information Seeking Behaviour of Learner in an Open University Libraries: Issues and Challenges - Sheela, V.; Shivaram, J. (Journal of Information and Knowledge, 2013)
Information Seeking is the process or activity of attempting to obtain information in both human and technological contexts. Information seeking is related to, but yet different from, information retrieval (IR). Much library and information science research is focused on the information seeking practices of practitioners in various fields of professional work. Studies have been carried out on the information seeking behaviour of librarians, academics, medical professionals, engineers and lawyers. Much of this research has been drawn on the work done by Leckw, Petttigrew and Sylvain, who in 1996 conducted an extensive review of the library and information science literature on information seeking behavior of professionals. Some experts report on a study concerned with understanding people‟s adaptation to new information searching environments. The experts have investigated how people with varying degrees of familiarity with information retrieval systems and varying models of information retrieval processes, interacted in an information retrieval system which did not support exact match retrieval with structured queries, but which did support best match ranked output retrieval with unstructured queries and automatic relevance feedback. The results include a classification of normal information retrieval strategies, the description of several adaptation strategies and the relationships between type and strength of people‟s mental models of information retrieval and their searching behaviours in the new information retrieval context.